Antibody-Based In Vivo Imaging of Central Nervous System Targets—Evaluation of a Pretargeting Approach Utilizing a TCO-Conjugated Brain Shuttle Antibody and Radiolabeled Tetrazines - Christoph Bredack; Martin R. Edelmann; Edilio Borroni; Luca C. Gobbi; Michael Honer (Pharmaceuticals, 2022)
Bioorthogonal pretargeted imaging using the inverse-electron-demand Diels–Alder (IEDDA) reaction between a tetrazine (Tz) and a trans-cyclooctene (TCO) represents an attractive strategy for molecular imaging via antibodies. The advantages of using a pretargeted imaging approach are on the one hand the possibility to achieve a high signal-to-noise ratio and imaging contrast; on the other hand, the method allows the uncoupling of the biological half-life of antibodies from the physical half-life of short-lived radionuclides. A brain-penetrating antibody (mAb) specific for β-amyloid (Aβ) plaques was functionalized with TCO moieties for pretargeted labeling of Aβ plaques in vitro, ex vivo, and in vivo by a tritium-labeled Tz. The overall aim was to explore the applicability of mAbs for brain imaging, using a preclinical model system. In vitro clicked mAb–TCO–Tz was able to pass the blood–brain barrier of transgenic PS2APP mice and specifically visualize Aβ plaques ex vivo. Further experiments showed that click reactivity of the mAb–TCO construct in vivo persisted up to 3 days after injection by labeling Aβ plaques ex vivo after incubation of brain sections with the Tz in vitro. An attempted in vivo click reaction between injected mAb–TCO and Tz did not lead to significant labeling of Aβ plaques, most probably due to unfavorable in vivo properties of the used Tz and a long half-life of the mAb–TCO in the blood stream. This study clearly demonstrates that pretargeted imaging of CNS targets via antibody-based click chemistry is a viable approach. Further experiments are warranted to optimize the balance between stability and reactivity of all reactants, particularly the Tz.